Optimum range of plasmid supercoiled DNA for preparation of ccompetent Top 10 E. coli - Muhammad Tahir Majeed; Khalid Hussain; Mamoona Noreen; Mateen Izhar (Archives of Global Professionals, 2011)
Objectives: In-house preparation of chemically competent andelectrocompetent Top 10 E. coli is not only economical butmeets the needs for most of the molecular cloning work. Forsuch transformations an optimum range of plasmidsupercoiled DNA is needed. Therefore, the present studydescribes the modification of two protocols for the preparationof such cells, and optimization of the amount of plasmidsupercoiled DNA required for better efficiency.Materials and methods: As most of the available protocols torender bacterial cells competent need special media orchemicals and are time consuming, the methods from HelenDonis-Keller Laboratory Manual of Washington University inSt. Louis and Goldberg Laboratory Standard Protocols of theUnited States Department of Agriculture have been used aftermeticulous selection and with few modifications for preparingchemically competent and electrocompetent Top 10 E. coli,respectively. The transformation was carried out using pUC19supercoiled plasmid DNA.Results: The transformation efficiencies of chemicallycompetent and electrocompetent Top 10 E. coli were found tobe 1.1 x 106 and 7.88 x 107 tranformants/μg of DNA,respectively. Such efficiencies are slightly higher than therequired (105-106 transformants/μg DNA) for most of thecloning experimentation.Conclusion: The results of the present study indicatethat for sufficient transformation competence rates theoptimum range of plasmid supercoiled DNA is 10 ng forchemically competent and 0.1 ng for electrocompetentTop 10 E. coli.